E-governance: An Approach to advancing Rural Development through IT Sector - Khan, Zubair Ahmed (International Journal of Computer Sciences and Engineering, 2025)
Among the emerging Asian economies, India is a nation with 70% of the population living in rural areas, which puts pressure on the government to focus more on the development of rural India. Information and communication technologies or ICTs act as providers of great opportunities for rural livelihoods and contribute to poverty reduction. The productivity of rural areas can be improved through the use of ICT and through various electronic governance initiatives such as E-Choupal, Akashganga, Gyandoot, Tata Kissan Kendra, Kissan Call Center, etc. in electronic form. Through this, the government can guarantee greater transparency and better administration. In this research paper, it is tried to identify different basic components that have led to rural development through various ICT initiatives.